Ginger (Zingiber officinale) dietary supplementation in mice regulates liver antioxidant defense systems in a dose- and age-dependent - Matin, Maima; Wysocki, Kamil; Horbańczuk, Jarosław Olav; Rossi, Luciana; Atanasov, Atanas G. (Frontiers in Pharmacology, 2025)
IntroductionOxidative stress and impaired antioxidant defenses contribute significantly to liver dysfunction, particularly with aging. This study evaluated the dose- and age-dependent effects of dietary ginger (Zingiber officinale) supplementation on liver antioxidant defense systems in mice.MethodsMale Swiss Webster mice aged 3, 6, and 12 months (n = 48 per age group) received standard feed or feed supplemented with either 0.6% or 1.8% dried ginger powder for 3 months. Liver tissue was analyzed for multiple antioxidant parameters, including DPPH radical scavenging activity, total antioxidant capacity, vitamin C levels, total phenolic content, superoxide dismutase (SOD) activity, malondialdehyde (MDA) levels, and reduced glutathione (GSH) concentrations.ResultsThe results demonstrated significant age-dependent declines in several antioxidant parameters in control animals, including DPPH scavenging activity, total antioxidant capacity, vitamin C levels, total phenolic content, and SOD activity. Ginger supplementation produced differential effects based on both dose and age. While 3-month-old mice showed decreased DPPH radical scavenging with ginger supplementation, both 6- and 12-month-old mice exhibited significantly increased activity. Higher-dose (1.8%) ginger supplementation enhanced GSH levels across all age groups, with effects being most pronounced in older mice. SOD activity remained unaffected by ginger supplementation across all groups. MDA levels were significantly reduced by 1.8% ginger supplementation in 3-month-old mice, with smaller, dose-dependent but non-significant reductions in older groups.DiscussionThese findings demonstrate that ginger’s effects on liver antioxidant systems are both dose- and age-dependent, with generally stronger beneficial effects observed at higher doses and in older animals. The observed dose- and age-dependent variations emphasize the importance of personalized supplementation strategies and provide a foundation for future research into the molecular mechanisms underlying ginger’s antioxidant effects.